A Flat Organizational Structure for an Inclusive, Interdisciplinary, International, and Undergraduate-Led Team - Palepu, Sriram; Nitsch, Alejandra; Narayan, Maitreyi; Kim, Stephany; Osier, Nicole (Nico) (Frontiers in Education, 2020)
Here, we describe our team’s approach to fostering an inclusive laboratory culture that executes a study in accordance with funder guidelines and research regulations, as well as provides volunteers with targeted mentorship, skill-development, and leadership opportunities. Our approach is five-pronged: (1) applying the principles of transformational leadership and kaizen, (2) establishing a strong mentor-mentee relationship and fostering community, (3) expanding the role of the research volunteer, (4) identifying volunteer leaders to (a) oversee and work alongside members of existing committees and (b) create new interconnected/interdisciplinary teams, and (5) using technology effectively. Our team is large; at the time of the initial submission we had 104 undergraduate/post-baccalaureate students with no graduate student supervision, and we have since grown to 118 members. Volunteers are diverse and come from 14 countries spanning 4 continents and numerous intersectional identities. We attribute our rapid expansion and diverse membership to our unique flat organization structure, which allows students from diverse backgrounds to work alongside the PI and contribute to improvements within the team, while fostering their own leadership skills. All volunteers are encouraged to take an active role in the lab, based on their strengths, experiences, and goals, and promote continuous improvement within the organization. Volunteers report feeling valued and have recruited new members from other groups they belong to, creating a self-sustaining system that allows aspiring professionals to learn from and lead their peers.